EVALUASI PROGRAM KAMPUNG KELUARGA BERENCANA DI KECAMATAN SANGATTA UTARA KABUPATEN KUTAI TIMUR - Taufik Hidayat; Aji Ratna Kusuma; Enos Paselle (Jurnal Administrative Reform, 2021)
This study aims to describe the results of the assessment by Family Planning Village Program in Swarga Bara Village, Sangatta Utara District. The research focus is input, process, output, supporting and inhibiting factors of the program. This research include by qualitative research with interview, observation, and documentation techniques, and then analyzed using an interactive analysis model and after that validity data tests use triangulation source. The research results show that the evaluation of the implementation Family Planning Village Program show that in general it has not been going well where by the input and process indicators show that from the implementation of increasing capacity of family planning extension workers in the field, provision of supporting facilities and infrastructure, budget support, resilience building and family empowerment and also advocacy and communication, information and education to that programs so many can not implemented and run well due to the minimal budget given, the lack of socialization by that program and nothing clear cooperation agreements between stakeholders only to service activities of Family planning that can run well while output indicators consisting of participant achievements of active family planning, participate activity group and then family data collection still relatively low because many achievements have not met the target sets.Keywords: Village Family Planning Program, Input, Process, Output.